CD44 alternative splicing senses intragenic DNA methylation in tumors via direct and indirect mechanisms. Issue 11 (4th June 2021) - Batsché, Eric; Yi, Jia; Mauger, Oriane; Kornobis, Etienne; Hopkins, Benjamin; Hanmer-Lloyd, Charlotte; Muchardt, Christian
Abstract: DNA methylation (meDNA) is a modulator of alternative splicing, and splicing perturbations are involved in tumorigenesis nearly as frequently as DNA mutations. However, the impact of meDNA on tumorigenesis via splicing-mediated mechanisms has not been thoroughly explored. Here, we found that HCT116 colon carcinoma cells inactivated for the DNA methylases DNMT1/3b undergo a partial epithelial to mesenchymal transition associated with increased CD44 variant exon skipping. These skipping events are directly mediated by the loss of intragenic meDNA and the chromatin factors MBD1/2/3 and HP1γ and are also linked to phosphorylation changes in elongating RNA polymerase II. The role of meDNA in alternative splicing was confirmed by using the dCas9/DNMT3b tool. We further tested whether the meDNA level could have predictive value in the MCF10A model for breast cancer progression and in patients with acute lymphoblastic leukemia (B ALL). We found that a small number of differentially spliced genes, mostly involved in splicing and signal transduction, are correlated with the local modulation of meDNA. Our observations suggest that, although DNA methylation has multiple avenues to affect alternative splicing, its indirect effect may also be mediated through alternative splicing isoforms of these meDNA sensors.